2012
DOI: 10.1155/2012/529829
|View full text |Cite
|
Sign up to set email alerts
|

Wood Volume Production and Use of 10 Woody Species in Semiarid Zones of Northeastern Mexico

Abstract: A research strategy was established to analyze the structure of timber trees in terms of forest productivity (volume and wood density) of 10 species. The native speciesAcacia farnesiana, Acacia schaffneri,Bumelia celastrina,Cercidium macrun,Condalia hookeri,Ebenopsis ebano,Helietta parvifolia, andProsopis laevigataand the exotic speciesEucalyptus camaldulensisandLeucaena leucocephalawere chosen due to their ecological and economic importance to the rural villages of northeastern Mexico. Measurements of differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 11 publications
1
6
0
6
Order By: Relevance
“…Table 9 shows that all the mechanical properties are classified as very high. The data reported by Carrillo et al (2011) and Foroughbakhch et al (2012) are similar to those reported in this study, so this species can be used in structural applications in construction. The mechanical properties can be compared with those of Acacia polyphylla.…”
Section: Shrinkagesupporting
confidence: 90%
See 1 more Smart Citation
“…Table 9 shows that all the mechanical properties are classified as very high. The data reported by Carrillo et al (2011) and Foroughbakhch et al (2012) are similar to those reported in this study, so this species can be used in structural applications in construction. The mechanical properties can be compared with those of Acacia polyphylla.…”
Section: Shrinkagesupporting
confidence: 90%
“…It is also regarded as a melliferous, medicinal species, and as food for goats and sheep (Foroughbakhch et al 2012, Carrillo et al 2011, Conafor 2008, González 2007, Rico 2001.…”
Section: Huicochea-santana and Barajas-morales (2002) Mention Some Chmentioning
confidence: 99%
“…This growth habit gives rise to a broad dispersed canopy, especially in poor or dry sites (Ramovs and Roberts, 2003;Burley, 1980 (15.84 m 2 ± 0.4 m 2 ; 2.86 m). Thus, all the tree species, except E. crebra, established and performed suitably (Table 4) ) but higher than the quantity produced by any native woody tree, which varied from for Prosopis laevigata according to Foroughbakhch et al (2012).…”
Section: Crown Developmentmentioning
confidence: 90%
“…The regional climate in the scheme of Köppen modified by García (2004) is defined as semiarid and subhumid [(A) C (Wo)] with two rainy seasons (summer and autumn) and a dry spell between November and April (Cavazos and Molina, 1992). According to Foroughbakhch et al (2012), September is the month with the highest precipitation (180-200 mm), and December and January with the lowest rainfall (15-20 mm).…”
Section: Description Of Experimental Site and Sampling Designmentioning
confidence: 99%